Managing anger : methods for a happier and healthier life - Luhn, Rebecca R. (Crisp Pub. Menlo ParkUS, 1992)
Defines anger; describes its causes; and its effects on our bodies, minds, relationships etc. Teaches how to control and manage personal anger; and how to cope with the anger of others.